Monotheism (from a sociopolitical and economic perspective) - Murat Iyigun (Institute for the Study of Labor (IZA), 2007)
The Axial Age, which lasted between 800 B. C. E. and 200 B. C. E., covers an era in which the spiritual foundations of humanity were laid simultaneously and independently in various geographic areas, and all three major monotheisms of Judaism, Christianity and Islam were born between 1200 B. C. E. and 622 C. E. in the Middle East. In this paper, I offer a taxonomy to comprehensively characterize the impact of monotheism on early economic development. Monotheist religions produced a paradigm shift in sociopolitical institutions because they (a) involve a strong degree of increasing returns to scale and the natural monopoly powers commensurate with it, (b) not only personalize the spiritual exchange relationship between the individual and the one deity, but also, due to the fact that this relationship extends into the afterlife as well, enhance individual accountability, and (c) expand their adherents' time horizon beyond biological life and impact the time discount between one's lifetime and the after-life. Taken together, these features suggest that the spread of monotheism ought to have promoted sociopolitical stability. Utilizing original historical data between 2500 B. C. E. and 1750 C. E. on 105 limited access orders, such as dynasties, kingdoms and empires, I show that monotheism had a positive and statistically significant impact on the length of reign as well as the average geographical size of social orders. Thus, I find empirical evidence that the birth and adoption of monotheistic religions aided early development both in the West and the Near East until the advent of the Industrial Revolution.
Keywords: 330; Economic development; religion; institutions; Religion; Institutionalismus; Entwicklung; Wirtschaftsgeschichte; Welt